Geogebra Training for Mathematics Teachers SDIT Insan Robbani North Lampung - Fhela Vhantoria Ningrum; Ratih Handayani; Khusnul Khotimah; Muinah (Pengabdian Kepada Masyarakat Cendekia, 2024)
One of the results of the preliminary study, namely interviews with SDIT Insan Robbani teachers, found problems with teachers finding it difficult to make flat shapes and geometric shapes in detail and detail. So far, math teachers only screenshot flat shapes from the internet or draw pictures manually. Geogebra is a solution to easily visualize flat shapes and spatial shapes. The purpose of community service is to increase the knowledge and abilities of the mathematics teacher at SDIT Insan Robbani North Lampung about mathematical software, namely Geogebra. Implementation methods include preliminary studies, problem identification, finding solutions and output targets, training, observing constraints, and evaluating PKM activities. The results achieved were an increase in the teacher's knowledge and abilities about the mathematical software, namely Geogebra. This was shown based on the results of the evaluation of PKM activities, the teacher was able to make 11 learning evaluation instruments in the form of geometry questions and GeoGebra-assisted flat shapes and 3 learning media in the form of video tutorials of flat shapes and GeoGebra-assisted room shapes.